Pendampingan Legalitas Usaha dan Sertifikasi Halal bagi Pelaku Industri Rumahan Pangan Olahan - Muh. Ma’ruf Idris; Edy Jumadi; Yana Fajriah; Eva Marin Sambo; Susianah Mochtar; Yudi Ahmad Sadeli; Bungatang Tahir; Annas Lallo (Lembaga Pengembangan Kinerja Dosen, 2026)
Sanrobone Village, Takalar, has great potential in the home-based processed food industry sector, but many business actors still do not have complete legality such as NIB, SPP-IRT, and halal certificates. This community service activity aimed to enhance business actors' knowledge and skills in managing legality and to assist the licensing process. The method employed was a one-day intensive training (8 hours) with an educative-participatory approach, conducted on May 5, 2026, at Sanrobone Village Hall with 24 participants. Results showed an increase in average knowledge scores from 28.33 to 80.83 (N-Gain=0.73, high category; p-value=0.000). Legality achievements: NIB 87.5% (21 participants), SPP-IRT 79.2% (19 participants), halal certification 83.3% (20 participants), and product labeling 91.7% (22 participants). Participant satisfaction was very high (4.52 out of 5; 91.7% scored ≥4). All 7 success indicators were achieved (100%). One-day intensive assistance is effective in enhancing understanding and ownership of business legality for processed food MSME actors, although continuous mentoring remains necessary to complete the licensing verification process.